Optimal Mini-grid for Rural Electrification: A Case Study of Sekoukou-Niger - Charles Ofori; Robert Ofosu; Ernest Atsu Ametepe (Jurusan Teknik Elektro Universitas Andalas, 2022)
The electricity access rate in Niger is one of the worst in Sub-Saharan Africa and is an issue of paramount importance to the Government of Niger. This energy insecurity has negatively affected industrialization and developmental plans, making Niger one of the poorest countries in the world. With a large landmass and several pockets of habitation in Niger, mini-grids remain the optimal way of providing electricity to people living in rural areas. Nigerienne Agency for the Promotion of Rural Electrification (ANPER), which is the institute responsible for rural electrification, currently operates about 110 diesel-powered mini-grids in Niger. With global warming looming, the operation of these diesel generators is not only expensive but also has an adverse effect on the environment. This paper seeks to analyze the techno-economic feasibility of a hybrid system for rural electrification in Niger with Sekoukou village as a case study. Load assessment, component technical configuration and component cost are simulated in HOMER software as objective functions to find the optimal size and cost. Results show that the most economical and efficient system for mini-grid operation in Sekoukou in Niger, is the generator-photovoltaic (PV) hybrid mini-grid which produces a levelized cost of energy of 0.271. A load shifting approach is applied to the existing load profile, which further reduces the levelized cost of energy from 0.271 to 0.177. This hybrid mini-grid system coupled with the load shifting approach would help improve the village’s ability and willingness to pay for electricity.